Study of the Effect of China’s Emissions Trading Scheme on Promoting Regional Industrial Carbon Emission Reduction - Feng, Rui; Lin, Peina; Hou, Chenxue; Jia, Shuaishuai (Frontiers in Environmental Science, 2022)
The creation of carbon emissions trading markets is a core policy for realizing China's twin objectives of reaching a peak in CO2 emissions before 2030 and achieving carbon neutrality by 2060. Given that industry is the most significant energy consumer and CO2 emitter, it is imperative to implement carbon reducing initiatives to attain these goals. Following the implementation of carbon emissions trading pilots in China, this article theoretically analyzes the mechanisms of action and paths of influence of China's carbon trading policies on regional industrial carbon emissions. Then, regarding the trading rights policies launched in 2013 as a quasi-natural experiment, this study uses provincial panel data and industry data from 2003 to 2016 to empirically test the effect of carbon trading on industrial emissions by employing the difference-in-difference and difference-in-difference-in-difference methods. It was found that carbon emissions trading can promote a reduction in regional industrial carbon emissions, achieving the dual aims of reducing total emissions and reducing emission intensity. The reduction effect occurs after the implementation of the carbon trading market policies. The carbon trading policies reduced regional industrial emissions by optimizing regional industrial structures and increasing regional technological innovation. It was also found that reductions in carbon emissions were heterogeneous among industries. These research conclusions will help to improve the top-level design of China's industrial energy saving and carbon reduction policies and to achieve low-carbon and green industrial development.